Correction: Ammonia borane–polyethylene oxide composite materials for solid hydrogen storage. Issue 11 (28th February 2018) - Nathanson, A. S.; Ploszajski, A. R.; Billing, M.; Cook, J. P.; Jenkins, D. W. K.; Headen, T. F.; Kurban, Z.; Lovell, A.; Bennington, S. M.
Abstract : Correction for 'Ammonia borane–polyethylene oxide composite materials for solid hydrogen storage' by A. S. Nathanson et al., J. Mater. Chem. A, 2015, 3, 3683–3691.